Oportunidades e desafios para implementação de projetos da indústria 4.0 na indústria farmacêutica - Silva, Leandro Simplicio (2023)
Industry 4.0 is becoming important as building a trend for technological changes in industry and the economy as a result of digital transformation. On the other hand, the pharmaceutical industry has a strong impact on social well-being and has been provoked into this new reality, not only by factors common to all industries, but also by the fact that it is a sector that creates additional barriers to the implementation of Industry 4.0 initiatives. This phenomenon occurs due to the conservative characteristics of the pharmaceutical industry, inherent to the documentary rigor of its processes. The objective of this study was to verify the relevant opportunities and challenges for implementing Industry 4.0 projects in the pharmaceutical industry. The methodology used in the research was a combination of literature analysis and research/field study with a qualitative-quantitative method, conducting interviews with experts in the pharmaceutical industry. 22 interviews were carried out with professionals from different functions in pharmaceutical companies, which provided plural perspectives, contributing to the breadth of the results of this study. The result was the presentation, in an organized manner, in order of relevance, of opportunities and challenges for the implementation of Industry 4.0 projects in the pharmaceutical industry.